Liquid–liquid phase separation enables chromatography-free purification and high-performance spidroin-amyloid hybrid silk fibers - Karin Tufvesson; Viktoria Langwallner; Tomas Bohn Pessatti; Gabriele Greco; Elin Karlsson; Sarah Stadlmayr; Axel Leppert; Michael Landreh; Anna Rising; Benjamin Schmuck (Proceedings of the National Academy of Sciences, 2026)
Large-scale production of artificial spider silk fibers requires heterologous expression of spider silk proteins (spidroins), yet current methods remain limited by low yields and costly purification processes. To overcome these challenges, we engineered mini-spidroins in which the poly-alanine motifs of the repetitive region were replaced with the non-natural amyloidogenic β16 peptide, significantly enhancing expression yields and solubility. Furthermore, we developed a simple, chromatography-free purification method for these constructs based on NaCl-induced liquid–liquid phase separation (LLPS). This one-step purification strategy reduced processing costs by up to 99% compared to conventional affinity chromatography while achieving yields of ~300 mg of purified protein per liter of shake flask culture and ~25 g L −1 from bioreactor cultivations. The purified engineered mini-spidroins could be spun into continuous fibers using an all-aqueous, biomimetic spinning process triggered by a pH drop. The resulting fibers exhibited mechanical properties comparable to those produced from the mini-spidroin NT2RepCT, which requires conventional chromatographic purification. Together, our protein-engineering approach and LLPS-based purification method provide a potentially scalable, sustainable, and cost-effective platform for artificial spider silk, representing a major step toward the commercial viability of recombinant silk-based materials.